Peningkatan Motivasi Belajar Remaja Masjid Jami Nurul Iman Cipedak Jagarkarsa - Muphimin, Muphimin; Faisal, Andri; Rambe, Delila; Barizki, Rezzi Nanda (Prisani Cendekia, 2025)
Many young people today tend to spend a significant amount of their time on unproductive or less meaningful activities. It is therefore essential to help them develop self-discipline and prepare for a future that demands resilience, skills, and purpose. Motivation plays a crucial role in empowering youth to strive for personal and academic growth. This community service activity was conducted at Nurul Iman Mosque, Cipedak, Jagakarsa, with the aim of increasing learning motivation among mosque teenagers. The primary method used was lecturing, which served as a means of knowledge transfer as well as motivational stimulation. Through a structured and interactive lecture format, participants were introduced to the importance of education, time management, and goal setting within both religious and personal development frameworks.The lecture received positive responses from the participants. Many showed enthusiasm, attentiveness, and active engagement during the sessions. Their interest reflected a readiness to internalize the messages delivered and apply them in their daily lives. The use of the lecture method proved effective in this context, particularly when combined with a motivational tone and relatable examples. It is hoped that this initiative will contribute to fostering a more positive learning culture among mosque youth and inspire them to pursue a better future through education and self-improvement.